Management Control System and the Case of CSR in the Tunisian Industrial Companies: What Findings by the Method of Structural Equation? - Dkhili, Hichem; Noubbigh, Hedi (International Review of Management and Marketing, 2013)
This study aims to the behavior of management control; it is providing a model to the behavior of integration of social responsibility in the management control tools. This model was validated with 306 Tunisian companies in the industrial sector. Through a questionnaire, the data collected are processed using exploratory and confirmatory analysis by the methods of structural equations. The results revealed that the management control system in industrial Tunisia is facing economic responsibility. This is in response to emerging pressures of uncertainty related to the environment, and in enrolling a strategy of domination by cost. In addition, the management control system is designed as a guidance tool actions and behaviors. Keywords: Management Control System; Corporate Social Responsibility; societal performance; Strategy; uncertainty environment JEL Classifications: M14; M41